The Effect of Discipline and Motivation on Employee Performance in PT Samsung Elektronik Indonesia - Ryani Dhian Parashakti; Muhamad Ekhsan (Kusuma Negara Business School, 2020)
This study aims to test and analyze the influence of discipline and motivation on PT Samsung Elektronik Indonesia. The data were collected by distributing questionnaires with a total sample of 92 respondents and using a quantitative descriptive approach. The data analysis used was statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially and simultaneously the discipline and motivation variables affect the performance of the employees of PT Samsung Elektronik Indonesia. This is evidenced by the results of the T test and the F test also shows the significant value of the two independent variables that support the hypothesis.